Angiopep-2 as an Exogenous Chemical Exchange Saturation Transfer Contrast Agent in Diagnosis of Alzheimer's Disease. (5th April 2022) - Wang, Chengguang; Lin, Guisen; Shen, Zhiwei; Wang, Runrun
Abstract : Background . Chemical exchange saturation transfer (CEST) is a novel imaging modality in clinical practice and scientific research. Angiopep-2 is an artificial peptide that can penetrate blood-brain barrier. The aim of this study was to explore the feasibility of Angiopep-2 serving as an exogenous CEST contrast. Methods . Phantoms of Angiopep-2 with different concentrations were prepared and then scanned using the 7.0T small animal MRI scanner. Different parameters including saturation powers and saturation duration were used to achieve the optimal CEST effect, and the optimal parameters were finally selected based on Z-spectra, asymmetric spectra, and phantom CEST imaging. CEST scanning of dimethyl sulfoxide (DMSO), the substance helping Angiopep-2 to be dissolved in water, was performed to exclude its contribution for the CEST effect. Results . A broad dip was observed from 2.5 to 3.5 ppm in the Z-spectra of Angiopep-2 phantoms. The most robust CEST was generated at 3.2 ppm when using formula ( M –3.2ppm  −  M +3.2ppm )/ M –3.2ppm . The CEST effect of Angiopep-2 was concentration dependent; the effect increased as the concentration increased. In addition, the CEST effect was more obvious as the saturation power increased and peaked at 5.5  µ T, and the CEST effect increased as the saturation duration increased. DMSO showed nearly 0% of the CEST effect at 3.2 ppm. Conclusions . Our results demonstrate that Angiopep-2 can act as an excellent exogenous CEST contrast. As it can penetrate blood-brain barrier and bind amyloid- β protein, amyloid- β targeting CEST, with Angiopep-2 as an exogenous contrast agent, can be potentially used as a novel imaging modality for early diagnosis of Alzheimer's disease. Collectively, Angiopep-2 may play a critical role in early diagnosis of Alzheimer's disease.